Schistosomiasis Japonica Control in Domestic Animals: Progress and Experiences in China - Cao, Zhiguo; Huang, Yinyin; Wang, Tianping (Frontiers in Microbiology, 2017)
Schistosomiasis japonica, caused by Schistosoma japonicum, is an endemic, zoonotic parasitic disease. Domestic animals, particularly bovines, are thought to play an important role in transmission of the disease. Historically, China was the country mostly severely impacted by schistosomiasis japonica, but now prevalence and morbidity have been greatly reduced. Since the mid-1950s when China launched the National Schistosomiasis Control Programme, the control of schistosomiasis in domestic animals has been carried out almost synchronously with that of human schistosomiasis, and this concept has been proven to be effective. Generally, the campaign of schistosomiasis japonica control in domestic animals in China went through four phases over the past six decades, namely, the large-scale epidemiological investigation phase, the case screening and small-scale chemotherapy phase, the mass chemotherapy phase, and the infection source control phase. These distinct phases were responsive to changing disease epidemiology, socioeconomic development, and technological advances, resulting in successful attainment of disease control goals.